Extraction and recovery of zinc, potassium, and sodium from blast furnace dust by ultrasonic-assisted ammonia leaching - Ju, Jiantao (Journal of Mining and Metallurgy, Section B: Metallurgy, 2026)
To efficiently recover valuable elements (Zn, K, Na) from blast furnace dust (BFD) and address issues such as alkali metal enrichment and disrupted furnace operation caused by its direct reuse, ammonia leaching experiments were conducted in this study using an NH3·H2O–NH4HCO3 system combined with ultrasound and ammonium persulfate. Single-factor experiments were performed to investigate the effects of variables such as [NH3]T and solid-to-liquid ratio on the leaching efficiencies of Zn, K, and Na under ultrasonic conditions. Under the conditions of [NH3]T = 6 mol·L−1, a solid-to-liquid ratio of 1:6, [NH3]/[NH4+] = 1:1, 40 °C, and 90 W ultrasound power, the leaching efficiencies of Zn, K, and Na reached 90.73%, 91.45%, and 91.56%, respectively. Based on these results, the effect of ultrasound combined with 1 mol·L−1 ammonium persulfate on zinc leaching was further evaluated, and the Zn leaching efficiency increased to 95.16%, while the leaching efficiencies of K and Na slightly increased to 92.35% and 92.50%, respectively. The enhanced Zn leaching is reasonably attributed to the synergistic effects of ultrasonic intensification and persulfate oxidation, in which ultrasound promotes particle fragmentation and mass transfer, while activated ammonium persulfate generates SO4•⁻ radicals that facilitate the oxidation of refractory ZnS. Kinetic analysis indicated that Zn leaching was mainly controlled by the surface chemical reaction, and ultrasound reduced the apparent activation energy from 62.37 to 44.15 kJ·mol−1. This synergistic leaching process, with high selectivity and low cost, provides theoretical and technical references for BFD resource recovery.
Keywords: blast furnace dust; zinc; Complex ammonia leaching; ultrasonic; ammonium persulfate